Loss of function of 1-FEH IIb has more impact on post-harvest inulin degradation in Cichorium intybus than copy number variation of its close paralog 1-FEH IIa - Dauchot, Nicolas; Raulier, Pierre; Maudoux, Olivier; Notté, Christine; Draye, Xavier; Van Cutsem, Pierre (Frontiers in Plant Science, 2015)
Key Message: The loss of mini-exon 2 in the 1-FEH IIb glycosyl-hydrolase results in a putative non-functional allele. This loss of function has a strong impact on the susceptibility to post-harvest inulin depolymerization. Significant variation of copy number was identified in its close paralog 1-FEH IIa, but no quantitative effect of copy number on carbohydrates-related phenotypes was detected. Inulin polyfructan is the second most abundant storage carbohydrate in flowering plants. After harvest, it is depolymerized by fructan exohydrolases (FEHs) as an adaptive response to end-season cold temperatures. In chicory, the intensity of this depolymerization differs between cultivars but also between individuals within a cultivar. Regarding this phenotypic variability, we recently identified statistically significant associations between inulin degradation and genetic polymorphisms located in three FEHs. We present here new results of a systematic analysis of copy number variation (CNV) in five key members of the chicory (Cichorium intybus) GH32 multigenic family, including three FEH genes and the two inulin biosynthesis genes: 1-SST and 1-FFT. qPCR analysis identified a significant variability of relative copy number only in the 1-FEH IIa gene. However, this CNV had no quantitative effect. Instead, cloning of the full length gDNA of a close paralogous sequence (1-FEH IIb) identified a 1028 bp deletion in lines less susceptible to post-harvest inulin depolymerization. This region comprises a 9 bp mini-exon containing one of the three conserved residues of the active site. This results in a putative non-functional 1-FEH IIb allele and an observed lower inulin depolymerization. Extensive genotyping confirmed that the loss of mini-exon 2 in 1-FEH IIb and the previously identified 47 bp duplication located in the 3′UTR of 1-FEH IIa belong to a single haplotype, both being statistically associated with reduced susceptibility to post-harvest inulin depolymerization. Emergence of these haplotypes is discussed.